The abundance of sucking insects on paddy field at Pekan Kandang, Melaka / Nur Asshifa Mohamed Azahar - Mohamed Azahar, Nur Asshifa (Faculty of Plantation and Agrotechnology, 2019)
The population abundance of sucking insects in paddy fields may causes losses towards farmer. Sucking insects can be divided into two groups which are plant sucking pest and grain sucking pest. The study was conducted to identify the population of sucking insect on paddy fields at Pekan Kandang, Melaka. There are two sampling method that were used to carry out this study which are yellow sticky trap and yellow pan trap. In each quadrant of 1m2, both of yellow sticky trap and yellow pan trap were placed randomly. The result shows three sucking insects which are rice bugs, thrips and mealy bugs. Descriptive analysis was conducted to determine the fluctuation of population rice bugs, thrips and mealybugs. Thus, the population abundance of rice bugs, trips and mealybugs were effect 2.5%, 6.4% and 2.1% respectively in different time of sampling. This project has succeeded one of its objectives which is to identify the population of sucking insects on paddy fields at Pekan Kandang Melaka because by using this method, the number of the insects can be identified.